Perancangan Sistem Layanan Informasi Pariwisata Berbasis Mobile Internet Dengan Menerapkan Konsep Mobile Interaction - Octhario, Raymond; Syafei, Wahyul Amien Syafei Amien; Chritiyono, Yuli (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
Mobile interaction is about the stuff of people’s lives, focused on understanding and developing blueprints for systems that permeate the broad spectrum of their  experiences.  People can use system,  They  can take  advantage of the system through mobile devices.  Due to limitations in the display and display media such as mobile phones in presenting and giving  information to the public.    the design of interaction  between  the  system  and  users  will  be  very  important,  It  is  a  thing  to  be  considered  to  create  a  mobile  internet-based information  systems.  Therefore,  the  application  of  mobile  interaction  design,  especially  in  terms  of  mobile  internet-based  system  is needed, so the system can be  used optimally.  Indonesia's tourism  sector  is one  sector of  the  service economy.  It  has  bright prospects  for mobile  interaction.  However  to  enhance  the  role  of  development  in  Indonesia,  is  still  one  of  many  shortcomings  that  limited  mediainformation services.    This study  concerns in  produce  and  information  service  system  especially  in  tourism  of  Palangka Raya  whichapply the concept  of  mobile  interaction  design.  To  apply the concept of  mobile  interaction,  there are  three  main  activities.  There  areunderstanding users, developing prototype designs and evaluation. Percentage points is higher in the evaluation, indicates that the user is able  to use  the system  and  interact  with  the system    and  based on feedback  from users, no complaints  are  ejected  from  the user  in  the system path. This provides an assessment of the success of the system design, system success and user satisfaction convey information to the system. Expected in the long periode, the system can increase tourism sector in the city of Palangka Raya.Keywords : Internet; Mobile Phones;  Information Services;  Mobile Interaction Design; Tourism